2018
DOI: 10.1097/jtn.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Radiation Exposure in Pediatric Trauma Related to Cervical Spine Clearance: A Quality Improvement Project

Abstract: Staff education and the use of an algorithm show promise in the reduction of radiation exposure and provide safe, effective clearance of the cervical spine in pediatric trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Repeat posttransfer CT was less common in transfers from nondesignated hospitals than Level III/IV trauma centers, probably because nondesignated hospitals are often large urban centers with the ability to transfer rapidly and to perform and transfer high‐quality advanced imaging. Similarly, the reduced odds of repeat posttransfer imaging in pediatric centers are likely to be related to better adherence to clinical guideline recommendations due to greater awareness of the impact of ionizing radiation in children in these centers 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat posttransfer CT was less common in transfers from nondesignated hospitals than Level III/IV trauma centers, probably because nondesignated hospitals are often large urban centers with the ability to transfer rapidly and to perform and transfer high‐quality advanced imaging. Similarly, the reduced odds of repeat posttransfer imaging in pediatric centers are likely to be related to better adherence to clinical guideline recommendations due to greater awareness of the impact of ionizing radiation in children in these centers 33 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the reduced odds of repeat posttransfer imaging in pediatric centers are likely to be related to better adherence to clinical guideline recommendations due to greater awareness of the impact of ionizing radiation in children in these centers. 33 A recent qualitative review identified the following root causes of low-value pretransfer CT imaging in trauma transfers in U.S. studies: meeting the expectations of the receiving center, legal responsibility, lack of clear clinical indications, and physicians' personal judgment. 32 In terms of low-value repeat posttransfer CT, 32 The influence of pretransfer CT on increased transfer time has also been observed in a U.S. study in patients with head injuries.…”
Section: Discussionmentioning
confidence: 99%
“…While cervical spine fractures occur in only 0.7% of all blunt trauma patients and constitute 19.38% of all spine fractured patients, failing to diagnose this relatively small proportion could lead to catastrophic neurologic disability. [ 8 ] The US modality provides a useful adjunct for emergency physicians in evaluating multiple trauma patients and achieving notable information in a short span of time. The current study enrolled and assessed severe multiple trauma patients with altered consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Four clinical decision-making tools utilized NEXUS criteria alone for initial clearance [22][23][24][25] ; however, 2 of these protocols limited the use of the tool to children over 3 years and 5 years, respectively. 23,24 Three additional protocols supplemented NEXUS with an additional novel clearance element. 15,16,19,26 To elaborate, the protocol in Sun et al 16 and McMahon et al, 15 whose studies utilized the same algorithm, added appropriate communication to NEXUS criteria; the protocol in Moore et al 19 added normal range of motion; and, the protocol in Chaudhry et al 26 added PEDSPINE criteria 2 (Supplemental Table 2A, Supplemental Digital Content 3, http://links.lww.com/SLA/D855).…”
Section: Triage Criteriamentioning
confidence: 99%
“…Despite the variability, when we assessed algorithm characteristics, we found that 12 of the 16 protocols (75%) incorporated some or all NEXUS criteria, either as initial touchpoints or embedded into the algorithm. Four clinical decision-making tools utilized NEXUS criteria alone for initial clearance [22][23][24][25] ; however, 2 of these protocols limited the use of the tool to children over 3 years and 5 years, respectively. 23,24 Three additional protocols supplemented NEXUS with an additional novel clearance element.…”
Section: Triage Criteriamentioning
confidence: 99%